2014
DOI: 10.1016/j.rmed.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar and intraparenchymal proteasome in sarcoidosis

Abstract: Patients with active sarcoidosis but not healthy controls demonstrate immunoproteasome in the lung tissue and in granulomas. Thus, the putative immune response in sarcoidosis may be mediated or sustained by the proteasomal system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…1c ). This is in line with a recent study that demonstrated expression of LMP2 and LMP7 in lung granulomas of sarcoidosis patients 24 . Our in vitro data show that primary alveolar type II cells and fibroblasts have the capability to express immunoproteasomes after IFNγ stimulation, thus enabling immunoproteasome-dependent antigen presentation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1c ). This is in line with a recent study that demonstrated expression of LMP2 and LMP7 in lung granulomas of sarcoidosis patients 24 . Our in vitro data show that primary alveolar type II cells and fibroblasts have the capability to express immunoproteasomes after IFNγ stimulation, thus enabling immunoproteasome-dependent antigen presentation.…”
Section: Discussionsupporting
confidence: 93%
“…While other studies have examined total levels of immunoproteasomes in human tissue, whole rat lungs, and in LCMV-infected mouse lungs and other organs 19 20 21 22 23 , cell-specific expression in the lung has not yet been investigated 23 24 . Here, we show that the immunoproteasomal subunit LMP2 is expressed at low basal levels in lung parenchymal cells (alveolar type I and II cells, fibroblasts) and the bronchial epithelium but strongly expressed in alveolar macrophages ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested elevated expression of immunoproteasome subunits in alveolar macrophages in patients with sarcoidosis. 54 Preliminary data of our group also suggest increased protein levels of LMP7 in BAL cells isolated from fibrotic lungs of bleomycin instilled mice. Future studies using LMP7-deficient mice will investigate the functional relevance of LMP7 activity for the course of bleomycin-triggered pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 72%
“…17 Misfolding and aggregation of serum amyloid A (SAA) might play an important role in sarcoidosis. 19 The microarray analysis of BALf cells performed by Gharib et al showed an important relationship between adaptive immunity and the proteasomal apparatus in this disease. 19 The microarray analysis of BALf cells performed by Gharib et al showed an important relationship between adaptive immunity and the proteasomal apparatus in this disease.…”
Section: Discussionmentioning
confidence: 96%
“…18 Immunoproteasome was markedly expressed in sarcoidosis tissues, its expression in BALf was disease-stage dependent. 19 The microarray analysis of BALf cells performed by Gharib et al showed an important relationship between adaptive immunity and the proteasomal apparatus in this disease. 20 Our analysis confirmed the increased expression of mRNA for interferon gamma (IFNG), a key regulator of the immunoproteasome as well as proteasome subunit beta 9 (PSMB9), PSMB10 and not significantly for PSMB8 in BALf cells of sarcoidosis compared to IPF patients.…”
Section: Probe Identifier Gene P-value Adjusted P-value Fold Changementioning
confidence: 96%